The conservation treatment of the B54 Japanese Armour from the Royal Armoury in Turin - Martina Trento (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The topic of this research and conservation work conducted on a Japanese armour coming from the Royal Armoury in Turin. The present work focuses on conservative issues involving a complex artifact such as samurai armours, which are known for being made of several materials like metals, lacquer, fabric, leather, skin, paper and horn. While all these materials can count on well-established conservation methodologies, the issues concerning lacquer applied on metal have rarely been studied by Western.